Banking system of Ukraine: trends and prospects of development - Zhavoronok, A.; Kholiavko, N. (Modern Science – Moderní věda, 2020)
The article analyzes the current state of the banking system of Ukraine, outlines the featuresof its functioning. It is determined that in recent years, in the context of structural reform of theeconomy in the banking services market, there have been such trends as:the rapid development ofinformation, including banking, technology that allow banks to expand the range of their servicesand products; restructuring of the financial and banking sectors, characterized by the emergence ofnew segments;increase of financial literacy of clients and a set of measures aimed at maintainingthe stable condition of domestic financial and credit institutions, timely neutralization andpreventing the development of destabilizing tendencies.
Keywords: bank, profitability, lending, deposits, capital, banking system.